Efektivitas Pendaftaran Jaminan Fidusia Secara Online oleh Notaris - Novia Betsy Clarissa; Siti Malikhatun Badriyah (Notarius, 2023)
AbstractThe development of the guarantee law brought tendencies to the guarantee institution. one of its products is a fiduciary guarantee which is quite appealing. With the online registration of fiduciary guarantees, it really has a one-of-a-kind mechanism from manual registration. This writing objectives to determine and examine the effectiveness of on-line registration of fiduciary guarantees by a Notary. The research technique used is normative juridical. This journal discusses the effectiveness of fiduciary guarantee registration which currently uses an internet system according with the law of the Minister of law and Human Rights wide variety 9 of 2013 regarding the Enforcement of digital Fiduciary assure Registration. The digital registration of fiduciary manner is finished through a notary reliable appointed by way of the financial institution or economic institution. but, there are nevertheless inhibiting elements within the online fiduciary registration system. The inhibiting factors are disturbances within the online machine, either on the overall legal administration internet site or non-Tax nation sales (PNBP) payments, incomplete records provided via the financial institution, and re-registration of fiduciary ensures. So these elements cause the net registration of fiduciary ensures to be ineffective.Keywords: effectiveness; fiduciary; online; notaryAbstrakPerkembangan aturan agunan membawa perkembangan pada forum jaminannya. Salah satu produknya merupakan agunan fidusia yang relatif diminati. Menggunakan diadakannya pendaftaran agunan fidusia secara online tentunya mempunyai mekanisme yang berbeda menggunakan registrasi secara manual. Penulisan ini bertujuan untuk mengetahui dan menganalisis efektivtas registrasi agunan fidusia secara online oleh Notaris. Metode penelitian yang dipergunakan ialah yuridis normatif. Artikel jurnal ini membahas efektivitas registrasi agunan fidusia yang saat ini sudah menggunakan server elektronik dimana pada Peraturan Menteri Hukum dan Hak Asasi Manusia nomor 9 Tahun 2013 tentang Pemberlakuan Pendaftaran Jaminan Fidusia secara Elektronik. Tahapan registrasi fidusia melalui langkah elektronik dilakukan oleh notaris yang ditunjuk bank ataupun ditunjuk oleh lembaga pembiayaan. Namun, masih terdapat kendala pada langkah-langkah registrasi fidusia secara online. Faktor-faktor penghambat tadi ialah gangguan pada sistem online baik pada website administrasi hukum umum ataupun pembayaran PNBP (Penerimaan Negara Bukan Pajak), data kurang lengkap diberikan oleh pihak bank, dan dilakukannya pendaftaran jaminan fidusia ulang, sehingga faktor-faktor tersebut menyebabkan pendaftaran jaminan fidusia melalui sistem online tidak efektif.Kata kunci: efektivitas; fidusia; online; notaris